Combined cognitive biases for pain and disability information in individuals with chronic headache: A preliminary investigation. (October 2018) - Schoth, Daniel E; Parry, Laura; Liossi, Christina
Pain-related cognitive biases have been demonstrated in chronic pain patients, yet despite theoretical predictions are rarely investigated in combination. Combined cognitive biases were explored in individuals with chronic headache ( n = 17) and pain-free controls ( n = 20). Participants completed spatial cueing (attentional bias), sentence generation (interpretation bias) and free recall tasks (memory bias), with ambiguous sensory-pain, disability and neutral words. Individuals with chronic headache, relative to controls, showed significantly greater interpretation and memory biases favouring ambiguous sensory-pain words and interpretation bias favouring ambiguous disability words. No attentional bias was found. Further research is needed exploring the temporal pattern of cognitive biases.